KONSTRUKSI TEOLOGI KRISTEN DALAM KONTEKS BUDAYA LOKAL SEBAGAI UPAYA MEMPERKUAT IMAN DAN PRAKSIS GEREJA - Jinersita Tappi; Sonia Bitti Patima; Winda Palembangan; Nuning Agustin (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the construction of Christian theology within the context of local culture as an effort to strengthen the faith and practice of the church in Indonesia. In a pluralistic social reality, the church is challenged to reinterpret the Christian faith to remain relevant to the dynamics of culture and the lives of its people. Through a contextual theological approach, this study highlights the importance of dialogue between God's revelation and local cultural values ​​imbued within society. Christian theology is understood as the foundation that strengthens the church's identity and spirituality, while local culture serves as the space in which faith takes root, grows, and bears fruit. The process of integrating the two produces a theology that is not only orthodox in its teachings but also orthopraxic in its concrete actions within society